Tacrolimus ointment 0.1% in the treatment of active patchy alopecia areata of childhood. - Sotiriou, E.; Patsatsi, A.; Fotiadou, C.; Sotiriadis, D.; Panagiotidou, D. (European Journal of Pediatric Dermatology, 2007)
Tacrolimus ointment 0.1% in the treatment of active patchy alopecia areata of childhood. Fourteen patients, 5 to 12 years of age, were enrolled into a single center open label study in order to initially assess the efficacy of tacrolimus ointment 0.1% in the treatment of patchy alopecia areata of the scalp. Patients applied the ointment twice daily for six months. A total of 3 patients did not complete the study. Five out of eleven patients (45%) showed significant hair regrowth. Our results show that tacrolimus ointment 0.1% may be an alternate therapeutic modality for short-standing, patchy and small-diameter lesions of alopecia areata in children. Therapeutic efficacy of any drug in patchy alopecia areata is doubted, as it is a self-limited disease. But even if regrowth is spontaneous and not induced by the formulation itself, the positive psychological impact of applying something, and moreover, else than a steroid cream, on the scalp is remarkably significant for little patients and their parents.